Flexible Terahertz Metamaterial Biosensor for Ultra-Sensitive Detection of Hepatitis B Viral DNA Based on the Metal-Enhanced Sandwich Assay - Li, Yumin; Wang, Xiaojing; Liu, Yu; Jin, Weidong; Tian, Huiyan; Xie, Fengxin; Xia, Ke; Zhang, Xiuming; Fu, Weiling; Zhang, Yang (Frontiers in Bioengineering and Biotechnology, 2022)
The high sensitivity and specificity of terahertz (THz) biosensing are promising and challenging in DNA sample detection. This study produced and refined a flexible THz MM biosensor for ultrasensitive detection of HBV in clinical serum samples based on gold magnetic nanoparticles-mediated rolling circle amplification (GMNPs@RCA) sandwich assay under isothermal conditions. Typically, solid-phase RCA reactions mediated by circular padlock probes (PLPs) are triggered under isothermal conditions in the presence of HBV DNA, resulting in long single-stranded DNA (ssDNA) with high fidelity and specificity. Then, the resultant ssDNA was conjugated with detection probes (DPs) immobilized on gold nanoparticles (DP@AuNPs) to form GMNPs-RCA-AuNPs Sandwich complexes. The HBV DNA concentrations were quantified by introducing GMNPs-RCA-AuNPs complexes into the metasurface of a flexible THz metamaterial-based biosensor chip and resulting in a red shift of the resonance peak of the THz metamaterials. This biosensor can lead to highly specific and sensitive detection with one-base mismatch discrimination and a limit of detection (LOD) down to 1.27 E+02 IU/mL of HBV DNA from clinical serum samples.The HBV DNA concentration was linearly correlated with the frequency shift of the THz metamaterials, within the range of 1.27 E+02～1.27 E+07 IU/mL, illustrating the applicability and accuracy of our assay in real clinical samples. This strategy constitutes apromising THz sensing method to identify virus DNA. In the future, it is hoped it can assist with pathogen identification and clinical diagnosis.